Bilateral paramedian thalamic syndrome: abnormal circadian wake-sleep and autonomic functions. Issue 6 (1st December 2002) - Montagna, P; Provini, F; Plazzi, G; Vetrugno, R; Gallassi, R; Pierangeli, G; Ragno, M; Cortelli, P; Perani, D
Abstract : Objectives: To describe wake-sleep and body core temperature (t°) rhythm abnormalities in two patients with bilateral paramedian thalamic calcifications. Methods: Patients underwent (18F)FDG PET scans and 24 hour polygraphic recordings of wake-sleep and t°. Results: PET showed bilateral thalamic hypometabolism in both patients with additional basal ganglia or mesiolateral frontal and cingular hypometabolism. Wake-sleep studies showed abnormal sleep organisation and in the case with frontal and limbic PET hypometabolism, pre-sleep behaviour associated with "subwakefulness" EEG activities, lack of EEG spindles and K complexes, and features of status dissociatus. The t° rhythms showed increased mesor in both (37.4°C and 37.75°C) and inverted rhythm in one patient. Conclusions: Paramedian thalamic structures and interconnected, especially frontal and cingular, areas play a part in the organisation of the wake-sleep cycle and attendant autonomic functions.